New NORMAL SEBAGAI POLITIK BONUM COMMUNE DI MASA PANDEMI - Adon, Mathias (Jurnal Budaya Nusantara, 2021)
The Covid-19 pandemic which engulfes the world has affected almost all nations, including Indonesia. This crisis caused the Indonesian government to face a dilemmatic choice. Implementing a lockdown to control the spread of Covid-19 actually ravaged the economy. It had no other alternative to save the economic sector than by forcing implementation of ‘the new normal’. This paper describes phenomenologically the implementation of the new normal policy in Indonesia using qualitative methods by exploring opinions and news items in Kompas newspaper, particularly how the Indonesian government's is moving the economic sector without sacrificing public welfare. The government considers the new normal as the most realistic step given the economic pressure and uncertainty about when Covid-19 will end. Therefore, new normal has become the bonum commune policy during the pandemic. The main principle of new normal as a political bonum commune is adapting one’s lifestyle in accordance with the health protocol.